Some factors influencing a career choices of the senior students of Gingoog City High School - Guanzon, Emilia S. Maye 1942-
Identifying the career choices of senior high school students is significant not only to educators, particularly guidance counselors, but also to an individual student. This study attempted to identify the choice of careers and some of the factors affecting the choice among senior students. A questionnaire and an inventory were administered to obtain the necessary information needed in the study. Findings of the study showed that there is a relationship between the career choices and the work attitudes of the senior students. Results of the study confirmed that career develop according to certain patters, thus needing a continuous program of career information and career guidance. Furthermore, there is a need for career education to aid the students in the successful development of their career.